TOBACCO DEPENDENCE TREATMENT WITH NICOTINE REPLACEMENT THERAPY AS ONE OF THE METHODS FOR CARDIOVASCULAR DISEASE RISK REDUCTION - O. V. Vikhireva; S. A. Shalnova; A. D. Deev (Рациональная фармакотерапия в кардиологии, 2015)
Aim. To investigate efficacy and safety of nicotine chewing gum and inhaler in individuals trying to quit smoking. To assess expected reduction of cardiovascular disease (CVD) and total mortality relative risks (RR).Material and methods. In this open, parallel study, 169 relatively healthy male smokers aged 18-60 years were randomly assigned to free choice vs admission of Nicorette gum (2/4 mg) or inhaler (10 mg). At baseline, all participants smoked ≥15 cig/d, for ≥3 years. The intervention phase lasted 3 months; follow-up evaluations were made at 3, 6 and 12 months after nicotine replacement therapy (NRT) initiation.Results. Twelve-month results were obtained for 152 subjects (response rate 89.9%). Point prevalence abstinence and reduction (smoking ≤50% of basic daily cigarette amount) rates were 19.7% and 35.5%, respectively. Neither abstinence, nor reduction rates depended on Nicorette form (gum vs inhaler), or on choice vs admission factor. The main predictors of long-term efficacy were nicotine dependence severity and contacts with other smokers.NRT was not associated with negative dynamics in objective health parameters (blood pressure, heart rate, ECG parameters, body weight, and body mass index) or self-evaluation of health. Both Nicorette forms seemed to be safe and well-tolerated.At 12 months, the expected mean RR reduction for CVD mortality reached 19%, for total mortality – 21%.Conclusion. In Russian clinical settings, NRT efficacy and safety are similar to that demonstrated in numerous international trials. NRT can be recommended as one of the methods of assistance to quit smoking and, therefore, for CVD risk reduction.